Criminal characteristics of bribery: concept, structure, value for forming a private investigation method - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2020)
In the article, the author analyzed the forensic characteristics of bribery, which is the theoretical basis for the formation of a private investigation technique for this group of crimes. The variety of views of forensic scientists on the formulation of the definition of the concept of «forensic characteristics of bribery». A significant difference in the author’s opinions on the structural construction of the forensic characteristics has been revealed, which is reflected in a large number of educational, scientific, methodological and practical literature, as well as in methodological recommendations directly addressed to practitioners of the investigative apparatus. For investigative activities, the author believes that the characteristic of bribery will be more meaningful and more valuable, in which elements of criminalistic significance are presented in more detail. The most significant elements for the forensic characteristic under consideration are the subject of bribery, the subject of a bribe, the method of committing a crime, the situation of the scene of the incident, and the mechanism for creating traces. Attention is also drawn to the need for an initial allocation in the structure of bribery of material elements, on the basis of which its criminalistic characteristics should be formed. The need for this is justified by the reality of the manifestations of the elements of the material structure of the crime in each individual case of its commission.